Studi Kasus Teman Sebaya Dalam Pembentukan Gaya Hidup Siswa - Arisa Darwis; Agung Rinaldy Malik; Burhan Burhan; Hasia Marto (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
ABSTRACT This study aims to describe the form of lifestyle, review how peer influence is in shaping the lifestyle and the negative impact of the student's lifestyle. The method in this research is qualitative research using a case study (case study). Sources of data in this study were students of SMA Negeri 1 Makassar who were selected using purposive sampling technique. The results of the study revealed that generally students make their lifestyle an effort to form an image. In addition, students seem extravagant and still depend on their parents in fulfilling their desires. Peers influence the formation of lifestyle through factors of imitation, suggestion, and sympathy. The negative impact in the formation of a lifestyle is a decrease in student achievement and motivation, changes in lifestyle that tend to be materialistic, and the formation of a pragmatic lifestyle. The conclusion of this research is that the influence of peer relations has a big impact on the student's lifestyle, so that it has more negative impacts. Keywords: Lifestyles, Peers.